Addressing Success: Fame and Narrative Strategies in Colette's La Naissance du jour - Juliette M. Rogers (Studies in 20th & 21st Century Literature, 1996)
Colette's La Naissance du jour (1928) is probably her most renowned work on the complex mother-daughter relations between her mother Sido and herself. Yet, as I demonstrate in this article, the book is just as much about renown itself. Beginning with the theoretical works of Leo Braudy (The Frenzy of Renown), John Rodden (The Politics of Literary Reputation), and a close analysis of La Naissance du jour, I look at the ways in which Colette manipulated her narratives to create her own public images ofherself. These manipulations would allow her to perpetuate the fame that she had enjoyed for the first twenty years of her writing career as a "daughter" figure, while simultaneously allowing her to begin to shape the public's reception of her to include a more mature authority figure for herself and her prose narratives in French literary circles of her day.
Keywords: Colette; La Naissance du jour; mother-daughter; mother; daughter; family; relations; renown; Leo Braudy; The Frenzy of Renown; John Todden; The Politics of Literary Reputation